2021
DOI: 10.3390/app11114811
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Blockchain Based SCM Systems with a Real Time Event Monitoring Function for Preemptive Risk Management

Abstract: The risk of supply chain disruption is usually related to daily disturbances in supply chain operations (e.g., demand fluctuations) and some emergency risks, such as earthquakes and epidemic outbreaks. During a crisis, companies need agility to quickly find new suppliers and open auxiliary sales channels to meet customer needs and remain competitive. However, identifying “event” is one of the most difficult challenges of current decision support systems. If the system encounters an emergency, it is usually una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…It also discusses the use of blockchain technology to increase plastic recycling and the circular economy Conceptual Risk, Resilience, and Sustainability Wong et al ( 2021 ) Sustainability (Switzerland) Technical sustainability of cloud-based blockchain integrated with machine learning for supply chain management The paper proposes the design of a robust blockchain architecture based on machine learning that is implemented on a cloud infrastructure Conceptual & Case Study Risk, Resilience, and Sustainability Blockchain, Cloud Computing, Machine Learning Liu et al, ( 2021a , b ) Sustainability (Switzerland) The sustainable development of financial topic detection and trend prediction by data mining The paper conducts data mining on 759 papers related to blockchain technology in the financial field using Web of Science bibliometrics data Literature Review Risk, Resilience, and Sustainability Runzel et al ( 2021 ) IEEE Consumer Electronics Magazine Designing a Smart Honey Supply Chain for Sustainable Development This article demonstrates how to build and deploy and open, image-based traceability system for sustainable development around the world. The intelligent distribution system is based on blockchain technology, pollen signature verification with machine learning algorithms, and a final customer information portal Conceptual Food & Agriculture Dadi et al ( 2021 ) Production Engineering Archives Agri-food 4.0 and innovations: Revamping the supply chain operations This paper presents a systematic review of the innovations in the agri-food for digital technologies such as internet-of-things, artificial intelligence, big data, RFID, robotics, block-chain technology, etc Literature Review Food & Agriculture Lee et al ( 2021 ) Applied Sciences (Switzerland) Enabling blockchain based scm systems with a real time event monitoring func...…”
Section: Methodsmentioning
confidence: 99%
“…It also discusses the use of blockchain technology to increase plastic recycling and the circular economy Conceptual Risk, Resilience, and Sustainability Wong et al ( 2021 ) Sustainability (Switzerland) Technical sustainability of cloud-based blockchain integrated with machine learning for supply chain management The paper proposes the design of a robust blockchain architecture based on machine learning that is implemented on a cloud infrastructure Conceptual & Case Study Risk, Resilience, and Sustainability Blockchain, Cloud Computing, Machine Learning Liu et al, ( 2021a , b ) Sustainability (Switzerland) The sustainable development of financial topic detection and trend prediction by data mining The paper conducts data mining on 759 papers related to blockchain technology in the financial field using Web of Science bibliometrics data Literature Review Risk, Resilience, and Sustainability Runzel et al ( 2021 ) IEEE Consumer Electronics Magazine Designing a Smart Honey Supply Chain for Sustainable Development This article demonstrates how to build and deploy and open, image-based traceability system for sustainable development around the world. The intelligent distribution system is based on blockchain technology, pollen signature verification with machine learning algorithms, and a final customer information portal Conceptual Food & Agriculture Dadi et al ( 2021 ) Production Engineering Archives Agri-food 4.0 and innovations: Revamping the supply chain operations This paper presents a systematic review of the innovations in the agri-food for digital technologies such as internet-of-things, artificial intelligence, big data, RFID, robotics, block-chain technology, etc Literature Review Food & Agriculture Lee et al ( 2021 ) Applied Sciences (Switzerland) Enabling blockchain based scm systems with a real time event monitoring func...…”
Section: Methodsmentioning
confidence: 99%
“…Other authors use blockchain technology as leverage for developing sound SC risk management approaches. For instance, in [39] the authors combine blockchain and a real-time event-monitoring system to track and disseminate emergent knowledge for preemptive management purposes. To improve visibility, the authors in [40] propose a blockchain-based SC network model.…”
Section: Classification Of the Retrieved Literaturementioning
confidence: 99%
“…Recently, a large body of studies has shown that the data along the supply chain can help protect the upstream and downstream companies in case there would be risk spillovers along the supply chain, thereby adversely affecting the target company (Wu et al, 2022). For instance, Osadchiy et al (2016) assert that credit risk can propagate in supply chain networks and exacerbate supplier production losses; supply chain data are applied to monitoring sudden inventory, sales fluctuations, and thus optimizing the structure of the supply chain (Ni et al, 2022); and also by monitoring data of the supply chain, Lee et al (2021) succeed in timely predicting the credit risk, all of which indicate that the data of the supply chain can serve as a complementary source for CRP.…”
Section: Credit Risk Predictionmentioning
confidence: 99%